An overview of the role of radionuclides in targeted cancer treatment: application of biomarkers for patient selection and developments to improve treatment efficacy - Smith, Tim A. D. (Frontiers in Oncology, 2025)
Radiopharmaceuticals for targeted radionuclide therapy (TRT) of tumours consist of a radionuclide conjugated to a component that can target the cancer. Several TRT radiopharmaceuticals have been licensed for the treatment of lymphoma, neuroendocrine and prostate cancers. The outcomes from two TRT trials, NETTER for neuroendocrine and VISION for prostate cancer, demonstrated beneficial outcomes. These findings have increased interest in the application of TRT in the treatment of prostate cancer and expansion to other cancer types. Patient selection for TRT is based on a measure of the overexpression of a target receptor on the cancer. To facilitate this, imaging is carried out using a similar targeting moiety to that used for treatment but labelled with an imaging radionuclide. Theragnostic pairs are selected to enable imaging and treatment with the same construct providing accurate predictions of the pharmacokinetics of the therapeutic in patients. This review covers the imaging biomarkers that act as companion diagnostics for TRT pharmaceuticals and the development of radiopharmaceuticals targeting other cancer types enabling expansion of TRT to these cancers. These include strategies to target cancer cells specifically and a pan-cancer approach by targeting fibroblast-activated protein (FAP) upregulated on cancer-associated fibroblasts (CAF). FAP-targeted radiopharmaceuticals are useful for diagnosis and staging but have drawbacks for TRT. Approaches to improve the efficacy of TRT including the use of high linear energy transfer (LET) alpha-emitters and pre-targeting and combination treatments are also covered. As described in this review, not all patients benefit from TRT making the case for predictive biomarkers. This is particularly important for the more damaging alpha emitters.